PENDAMPINGAN PENDIDIKAN KARAKTER MELALUI GERAKAN PRAMUKA - CAHYONO, ANANG; Tanjung Sari, Tita; Hadi, Ibnu (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The formation and instillation of children's character values ​​at SDN Kalianget Barat V is carried out through the scout movement which is packaged in the form of educamp activities. The instillation of these character values ​​is based on the problems that occur, including cases of bullying among students, lack of respect for teachers, low levels of student discipline and lack of student self-confidence. The purpose of this PkM activity is to instill children's character values ​​from an early age through mentoring of extracurricular scout activities held every Saturday. The methods implemented in this activity include three stages including: first, the preparation stage (initial observation, problem formulation, PkM objectives), second the implementation stage and third, the evaluation stage. The implementation of this PkM activity is carried out every Saturday by providing material on character education and material on scout skills I, II and III and practicing it outside the classroom as a form of educamp activity. The results of the implementation of Pk Mini went very smoothly and in accordance with the expected goals, this was proven by the enthusiasm of the participants or students to participate in the event because they were given encouragement and motivation by the speakers. Overall, character education assistance through the scouting movement packaged in this educamp can have a positive impact on students, especially in instilling character values ​​from an early age.